Expressions of HPV 16-E6 in esophageal carcinoma and its clinical significance - Zhao, Xing; Sahi, Rajina; Zhao, Yu-Yang; Wang, Jun; Li, Chun-Hui (Journal of Advances in Internal Medicine, 2017)
Aim: The aim of the study was to explore the association between HPV16-E6 protein and esophageal squamous cell carcinoma. Methods: SP immunohistochemical method was used to examine the expression of HPV 16-E6 in 50 cases of esophageal squamous cell carcinoma, 10 cases of normal esophageal squamous cell and 10 cases of adjacent tissue. Result: The expressions of HPV 16-E6 was significantly higher in esophageal carcinoma than in normal esophageal mucosa and in adjacent tissue. The expressions of HPV 16-E6 had a significant correlation with invasive depth (P<0.05), but not with the patient age, lymph node metastasis and tumor size (P>0.05). Conclusion: HPV 16-E6 can promote the growth and metastasis of esophageal squamous cell carcinoma and can be a prognostic factor of esophageal squamous cell carcinoma.